Biofilm formation by marine bacteria is impacted by concentration and surface functionalization of polystyrene nanoparticles in a species‐specific manner. Issue 2 (6th February 2020) - Okshevsky, Mira; Gautier, Eva; Farner, Jeffrey M.; Schreiber, Lars; Tufenkji, Nathalie
Summary: The world's oceans are becoming increasingly polluted by plastic waste. In the marine environment, larger plastic pieces may degrade into nanoscale (<100 nm in at least one dimension) plastic particles due to natural weathering effects. We observe that the presence of 20 nm plastic nanoparticles at concentrations below 200 ppm had no impact on planktonic growth of a panel of heterotrophic marine bacteria. However, the presence of plastic nanoparticles significantly impacted the formation of biofilms in a species‐specific manner. While carboxylated nanoparticles increased the amount of biofilm formed by several species, amidine‐functionalized nanoparticles decreased the amount of biofilm of many but not all bacteria. Further experiments suggested that the aggregation dynamics of bacteria and nanoparticles were strongly impacted by the surface properties of the nanoparticles. The community structure of an artificially constructed community of marine bacteria was significantly altered by exposure to plastic nanoparticles, with differently functionalized nanoparticles selecting for unique and reproducible community abundance patterns. These results suggest that surface properties and concentration of plastic nanoparticles, as well as species interactions, are important factors determining how plastic nanoparticles impact biofilm formation by marine bacteria.